2018
DOI: 10.1177/0972150918803992
|View full text |Cite
|
Sign up to set email alerts
|

Presence and Sources of Contrarian Profits in the Bangladesh Stock Market

Abstract: This article, using weekly data for the period 2002 through 2013, investigates the presence of both contrarian and momentum profits and their sources in the Bangladesh stock market. It follows the methodology of Lo and MacKinlay ( Review of Financial Studies, 1990, 3(2), 175–205) to form portfolios with a weighted relative strength scheme (WRSS). The methodology of Jegadeesh and Titman ( Review of Financial Studies, 1995, 8(4), 973–993) is used to decompose the contrarian/momentum profits into three elements: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…De Bondt and Thaler, proponents of this strategy, have found a significant advantage in the American stock market. (Ma et al, 2018) found it on the exchanges of several Asian countries, namely China, Hong Kong, Japan, Korea, Malaysia, Singapore, and Taiwan (Chowdhury et al, 2019) found these profits in the Bangladesh market (Reddy et al, 2020) in Shanghai market, and (Truong et al, 2023) in Ho Chi Minh Stock Exchange (HOSE) Vietnam. (Truong et al, 2023) Found the anomaly and, at the same time, also supported the hypothesis that the Vietnam stock market is inefficient in its weak form, so the investors can earn abnormal returns using the contrarian investment strategy.…”
Section: Introductionmentioning
confidence: 99%
“…De Bondt and Thaler, proponents of this strategy, have found a significant advantage in the American stock market. (Ma et al, 2018) found it on the exchanges of several Asian countries, namely China, Hong Kong, Japan, Korea, Malaysia, Singapore, and Taiwan (Chowdhury et al, 2019) found these profits in the Bangladesh market (Reddy et al, 2020) in Shanghai market, and (Truong et al, 2023) in Ho Chi Minh Stock Exchange (HOSE) Vietnam. (Truong et al, 2023) Found the anomaly and, at the same time, also supported the hypothesis that the Vietnam stock market is inefficient in its weak form, so the investors can earn abnormal returns using the contrarian investment strategy.…”
Section: Introductionmentioning
confidence: 99%
“…De Haan and Kakes (2011) study the use of contrarian strategies by institutional investors. Other works, such as Dhankar and Maheshwari (2014), Shi et al (2015), Doan et al (2016), Shah and Shah (2018), Chen et al (2018), Chowdhury et al (2019), Munir et al (2022), Day and Ni (2023), Jagirdar and Gupta (2023) and Qashqai et al (2023), evaluate the performance of contrarian strategies in various markets.…”
Section: Introductionmentioning
confidence: 99%
“…This study focuses on the stock markets of Bangladesh, India, and Pakistan for two reasons. First, several studies argue that these stock markets are mostly dominated by small investors and noise trading (Brzeszczyński et al, 2015; Chowdhury et al, 2019; Cuthbertson & Nitzsche, 2005; Iqbal, 2012). The investment decisions of small investors in the South-Asian markets are driven by either sentiments or past share price movements which leads to greater price volatility in these markets (Brzeszczyński et al, 2015; Chowdhury et al, 2019; Naik & Reddy, 2021; Shiller, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…First, several studies argue that these stock markets are mostly dominated by small investors and noise trading (Brzeszczyński et al, 2015; Chowdhury et al, 2019; Cuthbertson & Nitzsche, 2005; Iqbal, 2012). The investment decisions of small investors in the South-Asian markets are driven by either sentiments or past share price movements which leads to greater price volatility in these markets (Brzeszczyński et al, 2015; Chowdhury et al, 2019; Naik & Reddy, 2021; Shiller, 1990). In addition, the noise trading further contributes toward enhanced risk in the short term, thereby offering unique justifications for the time-varying return patterns of stock market anomalies.…”
Section: Introductionmentioning
confidence: 99%